Methaemoglobinemia Induced by MDMA? - L. L. W. Verhaert (Case Reports in Pulmonology)
Case. A 45-year-old man with a blank medical history presented at the emergency room with dizziness and cyanosis. Physical examination showed cyanosis with a peripheral saturation (SpO2) of 85%, he did not respond to supplemental oxygen. Arterial blood gas analysis showed a striking chocolate brown colour. Based on these data, we determined the arterial methaemoglobin concentration. This was 32%. We gave 100% oxygen and observed the patient in a medium care unit. The next day, patient could be discharged in good condition. Further inquiry about exhibitions and extensive history revealed that the patient used MDMA (3,4- methylenedioxymethamphetamine, the active ingredient of ecstasy). Conclusion. Acquired methaemoglobinemia is a condition that occurs infrequently, but is potentially life threatening. Different nutrients, medications, and chemicals can induce methaemoglobinemia by oxidation of haemoglobin. The clinical presentation of a patient with methaemoglobinemia is due to the impossibility of O2 binding and transport, resulting in tissue hypoxia. Important is to think about methaemoglobin in a patient who presents with cyanosis, a peripheral saturation of 85% that fails to respond properly to the administration of O2. Because methaemoglobin can be reduced physiologically, it is usually sufficient to remove the causative agent, to give O2, and to observe the patient.